Long-Term Performance Comparison of Bipolar Active vs. Quadripolar Passive Fixation Leads in Cardiac Resynchronisation Therapy - Schiedat, Fabian; Bogossian, Harilaos; Schöne, Dominik; Aweimer, Assem; Patsalis, Polykarpos C.; Hanefeld, Christoph; Mügge, Andreas; Kloppe, Axel (Frontiers in Cardiovascular Medicine, 2021)
Background: Bipolar active fixation (BipolarAFL) and quadripolar passive fixation left-ventricular leads (QuadPFL) have been designed to reduce the risk of phrenic nerve stimulation (PNS), enable targeted left-ventricular pacing, and overcome problems of difficult coronary venous anatomy and lead dislodgment. This study sought to report the long-term safety and performance of a BipolarAFL, Medtronic Attain Stability 20066, compared to QuadPFL. Methods: We performed a single-operator retrospective analysis of 81 patients receiving cardiac resynchronization therapy (CRT) (36 BipolarAFL, 45 QuadPFL). Immediate implant data and electrical and clinical data during follow-up (FU) were analyzed. Results: BipolarAFL has been chosen in patients with significantly larger estimated vein diameter (at the lead tip: 7.2 ± 4.1 Fr vs. 4.1 ± 2.3 Fr, p < 0.001) without significant time difference until the final lead position was achieved (BipolarAFL: 20.9 ± 10.5 min, vs. QuadPFL: 18.9 ± 8.9 min, p = 0.35). At 12 month FU no difference in response rate to CRT was recorded between BipolarAFL and QuadPFL according to left ventricular end-systolic volume (61.1 vs. 60.0%, p = 0.82) and New York Heart Association (66.7 vs. 62.2%, p = 0.32). At median FU of 48 months (IQR: 44–54), no lead dislodgment occurred in both groups but a significantly higher proportion of PNS was recorded in QuadPFL (13 vs. 0%, p < 0.05). Electrical parameters were stable during FU in both groups without significant differences. Conclusion: BipolarAFL can be implanted with ease in challenging coronary venous anatomy, shows excellent electrical performance and no difference in clinical outcome compared to QuadPFL.